(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In the past years, a great work has been done for Chinese, Japanese, Korean, Latin, Arabic and Indic scripts handwriting recognition (HWR). Handwriting recognition is the process to understand handwritten text. The handwritten text can be written on the paper or digital surfaces. When the handwritten text written on the paper is first scanned and then understood by the computer, it is called offline handwriting recognition. But on the other hand, when the handwritten text is understood while writing on the digital surface, it is called online handwriting recognition. Thus, an online handwriting system can recognizeunderstand digitally handwritten strokes, characters, words and sentences. Online handwritten word recognition (OHWR) system has various phases like data collection and preprocessing, segmentation of strokes, feature extraction, classification and post processing etcetera. The present work has been done for online handwriting recognition in Tamil and Devanagari Indic scripts. This work has been done for online handwriting recognition of larger units (words). The key results presented in this work have been obtained from reputed journals and conferences of pattern recognition and handwriting recognition as Pattern Analysis and Machine Intelligence (PAMI), Pattern Recognition(PR), Pattern Recognition Letters (PRL), International Journal on Document Analysis and Recognition(IJDAR) , International Conference on Document Analysis and Recognition (ICDAR) and International Conference on Frontiers in Handwriting Recognition (ICFHR) etcetera.